Certified Ethical Hacker (CEH) preparation guide : lesson-based review of ethical hacking and penetration testing - Sheikh, Ahmed (Apress L.P., 2021)
Know the basic principles of ethical hacking. This book is designed to provide you with the knowledge, tactics, and tools needed to prepare for the Certified Ethical Hacker(CEH) exam -- a qualification that tests the cybersecurity professional's baseline knowledge of security threats, risks, and countermeasures through lectures and hands-on labs. You will review the organized certified hacking mechanism along with: stealthy network re-con; passive traffic detection; privilege escalation, vulnerability recognition, remote access, spoofing; impersonation, brute force threats, and cross-site scripting. The book covers policies for penetration testing and requirements for documentation. This book uses a unique "lesson" format with objectives and instruction to succinctly review each major topic, including: footprinting and reconnaissance and scanning networks, system hacking, sniffers and social engineering, session hijacking, Trojans and backdoor viruses and worms, hacking webservers, SQL injection, buffer overflow, evading IDS, firewalls, and honeypots, and much more. You will: Understand the concepts associated with Footprinting Perform active and passive reconnaissance Identify enumeration countermeasures Be familiar with virus types, virus detection methods, and virus countermeasures Know the proper order of steps used to conduct a session hijacking attack Identify defensive strategies against SQL injection attacks Analyze internal and external network traffic using an intrusion detection system